Distribution of human papillomavirus genotypes by severity of cervical lesions in HPV screened positive women from the ESTAMPA study in Latin America. - Rita Mariel Correa; Armando Baena; Joan Valls; María Celeste Colucci; Laura Mendoza; Maryluz Rol; Carolina Wiesner; Annabelle Ferrera; María Dolores Fellner; Joaquín Víctor González; Jorge Alejandro Basiletti; Pamela Mongelos; et al. (PLoS ONE)
The proportion of HPV16 and 18-associated cervical cancer (CC) appears rather constant worldwide (≥70%), but the relative importance of the other HR-HPV differs slightly by geographical region. Here, we studied the HPV genotype distribution of HPV positive Latin American (LA) women by histological grade, in a sub-cohort from the ESTAMPA study; we also explored the association of age-specific HPV genotypes in severe lesions. Cervical samples from 1,252 participants (854 ≤CIN1, 121 CIN2, 194 CIN3 and 83 CC) were genotyped by two PCRs-Reverse Blotting Hybridization strategies: i) Broad-Spectrum General Primers 5+/6+ and ii) PGMY9/11 PCRs. HPV16 was the most frequently found genotype in all histological grades, and increased with the severity of lesions from 14.5% in ≤ CIN1, 19.8% in CIN2, 51.5% in CIN3 to 65.1% in CC (p < 0.001). For the remaining HR-HPVs their frequency in CC did not increase when compared to less severe categories. The nonavalent vaccine HR-types ranked at the top in CC, the dominant ones being HPV16 and HPV45. HR-HPV single infection occurs, respectively, in 57.1% and 57.0% of ≤CIN1 and CIN2, increasing to 72.2% and 91.6% in CIN3 and CC (p<0.001). No association between age and HPV type was observed in CC, although the risk of HPV16 infection in CIN3 cases increased with age. Results confirm the relevance of HPV16 in the whole clinical spectrum, with a strong rise of its proportion in CIN3 and cancer. This information will be relevant in evaluating the impact of HPV vaccination, as a baseline against which to compare genotype changes in HPV type-specific distribution as vaccinated women participate in screening in LA region. Likewise, these data may help select the best HPV testing system for HPV-based efficient, affordable, and sustainable screening programmes.